A case of pathological complete regression in combined modality treatment of resectable Her2/neu-positive gastric cancer - A. V. Avgustinovich; S. G. Afanasyev; L. V. Spirina; E. V. Kaygorodova; R. V. Ermolenko; E. N. Samtsov; I. G. Frolova; O. V. Cheremisina (Сибирский онкологический журнал)
Background. Overexpression of Her2neu occurs in 15–20% of patients with gastric cancer and correlates with an unfavorable prognosis. Case report. We report a case of pathological complete regression of resectable gastric cancer with Her2/neu overexpression. The patient received combined modality treatment including 8 cycles of neoadjuvant chemotherapy with mFLOT + trastuzumab followed by R0 resection. The addition of targeted therapy did not have a negative impact on the perioperative period. Histolohical examination of the surgical specimen revealed pathological complete response (Mandart TGR1). Currently, the patient has been followed-up for 27 months without signs of disease relapse. Conclusion. Total neoadjuvant chemotherapy with mFLОТ+ trastuzumab for operable gastric cancer with Her2/neu overexpression allows us to hope for improved long-term treatment outcomes.